Facebook and Public Opinion Formation in Nigeria - Solomon Blessing Tsokwa; Brown George Nathan; Okpalike Vivian Ifeoma (ALSYSTECH Journal of Education Technology, 2026)
With more than 27 million users in Nigeria, Facebook has emerged as an influential platform for public opinion formation. This study examines how Facebook shapes public opinion in Nigeria, focusing on its content algorithm, sponsored advertisements, and user-generated content. Drawing on agenda-setting theory, social learning theory, and selective exposure theory, the study analyzes the mechanisms through which information exposure and user engagement influence public perceptions. The findings indicate that Facebook’s extensive reach, algorithmic content curation, sponsored advertising, and user-generated content substantially contribute to opinion formation. However, the platform also facilitates the dissemination of misinformation, reinforces echo chambers, and enables hate speech and incitement to violence. The study concludes that Facebook plays a significant yet potentially disruptive role in Nigeria’s public sphere. It recommends greater transparency in content algorithms, stronger fact-checking mechanisms, effective regulation of hate speech and misinformation, increased user awareness of cognitive bias, expanded media literacy campaigns, and collaboration between Facebook and government agencies to protect democratic values and institutions. The study contributes to understanding digitally mediated public opinion in Nigeria and underscores the importance of platform accountability, media literacy, and responsible user engagement.